Components and antibacterial activity of a novel essential oil from the nutrient broth of Eremothecium ashbyii H4565. (March 2019) - He, Feng; Li, Ke; Zhang, Xiaohong; Yang, Ying; Fang, Yuanping; Xiang, Fu
Abstract: Food spoilage is a global issue, and millions of people suffer from food-borne infections. So it is urgent to search for novel, effective and safe antimicrobial agents. A novel essential oil was obtained from Eremothecium ashbyii H4565, which was identified and conserved in the China Center for Type Culture Collection. The chemical components of the essential oil were analyzed by gas chromatography-mass spectrometry. The results showed that 22 components were identified, and the major compounds were geraniol, citronellol, phenylethyl alcohol, longifolene, linalool and nerolidol. By disc diffusion assay and double-broth dilution method, the essential oil exhibited antibacterial activities against food spoilage microbes, such as Staphylococcus aureus, Bacillus subtilis, Bacillus cereus, Listeria monocytogenes, Escherichia coli, Salmonella typhimurium, Zygosaccharomyces bailii, Saccharomyces cerevisiae, and Candida utilis . The minimum inhibition concentrations of the essential oil against these microorganisms were 15.6, 15.6, 15.6, 15.6, 7.8, 7.8, 31.2, 15.6, and 31.2 μg/mL, respectively. Based on the results of electron microscopy, protein and DNA leakage, and cytoplasmic membrane permeability, the possible antibacterial mechanism was indicated that cell wall and cytoplasmic membrane were destroyed as the targets by the essential oil.. Therefore, it was suggested that essential oil might be used as a potential antimicrobial agent in food. Highlights: A novel essential oil was obtained from the nutrient broth of Eremothecium ashbyii H4565. The components of the essential oil was analyzed by GC-MS. The essential oil exhibited strong antibacterial activities. The targets of the essential oil might be the cell wall and membrane.